FACIES ANALYSIS AND ROCK TYPE DISTRIBUTION IN UPPER INTERVAL OF BATURAJA FORMATION, KRISNA FIELD, SUNDA BASIN - AGENG PRIMA SAKTI, CHANDRA
Krisna Field is one of carbonate field in western part of South East Sumatra (SES) Block, Sunda Basin. Main reservoir of the study is carbonate upper Baturaja Formation that already developed since 1980 using 30 wells and contributed about 25% from whole oil production in Central Business Unit, SES Block. Production data showed that there are problems about heterogenity and conectivity reservoir, so reservoir characteristic study is very important to be done. The objectives of this study are lithofacies identification, facies assosiation identification, rock type distribution, porosity distribution, and permeability distribution. Petrographic analysis using thin section from 2 core sample Krisna D-04 and Krisna E-02 well, showed that there are 5 lithofacies, foraminifera shale, planktonic foraminifera packstone, skeletal wackestone, skeletal packstone, and bentic foraminifera packstone. Lithofacies identification supported by seismic atribute mean amplitude for geometry boundary, showed there are 2 facies assossiation, skeletal mound and slope to basin, that interpreted as reef complex before the study done. Rock type identification using Pore Geometry Structure (PGS) resulted 6 rock type (RT), and recognized that RT1 interparticle-moldic micropore assossiation, RT2 interparticle mesopore assossiation, RT3 interparticle-moldic mesopore assossiation, RT4 interparticle-moldic macropore assossiation, RT5 vuggy-moldic macropore assossiation, and RT6 vuggy-channeling assossiation. Rock type distibution using stochastic method in skeletal mound facies assossiation, controlled porosity and permeability distribution. The study showed that rock type, porosity, and permeability distribution are main factor of heterogenity and conectivity reservoir carbonate upper Baturaja Formation. The study results will be used as main input of dynamic simulation for water injection and further development plan in Krisna Field, Sunda Basin.